Tafonomia dos Pygocephalomorpha (Crustacea, Peracarida, Malacostraca), Permiano, Bacia do Paraná, Brasil, e seu significado paleoambiental - Matos, Suzana Aparecida (2013)
Taphonomy of the pygocephalomorpha (Crustacea, Peracarida, Malacostraca), Permian, Paraná Basin, Brazil, and its paleoenvironmental meaning. Crustaceans (Pygocephalomorpha, Peracarida) are the main fossil invertebrates recorded in the Early Permian Assistência Formation, Irati Subgroup, State of São Paulo, Paraná Basin. For this study, samples taken from the base of the Ipeúna Member, Bairrinho Bed, State of São Paulo, were analyzed and complemented by fossils from the Irati Formation, State of Rio Grande do Sul. The taphonomic spectrum of the pygocephalomorphs includes three main preservational modes: Type 1. Complete pygocephalomorphs (with outstretched or flexed abdomen), which are associated to cream-colored mudstones and more commonly to black shales. In rare cases, molds of soft parts are preserved. They suffered rapid burial (hours to days) by mud blankets associated to storm events in anoxic bottoms, below storm wave base with minimum bottom disruption, followed by low rates of background sedimentation; Type 2. Partly articulated (carapace and abdomen, with or without caudal fan and without appendages) pygocephalomorphs, with extended or flexed abdomen, which are present in cream-colored pelites, associated with hummocky cross-stratifications, intercalated with black shales. These may represent individuals or remains lying in the sediment-water interface preserved by rapid burial associated to episodic sedimentation events; Type 3. Disarticulated pygocephalomorphs, with isolated carapaces, abdomen, or abdominal segments. This is the predominant preservational mode in our samples. The skeletal remains can be found isolated or in dense, bioclast-supported concentrations (micro-coquines), representing proximal to distal tempestites. Finally, the extreme preservational quality seen in crustaceans of the Type 1 recorded in black shales, occasionally with molds of soft parts, indicates that the host rocks may represent Konservat-Lagerstätten deposits, as already suggested to coeval occurrences of the Irati Formation in Uruguay. © 2013 by the Sociedade Brasileira de Paleontologia.